An artificial intelligence-based sustainable halalan toyyiban supply chain knowledge dissemination system: the conceptual model - Omar, Mohd Misron; Shadan, Hezlin; Md Akhir, Romiza; M. Misron, M. Faris (Faculty of Information Management, 2025)
The issue involving non-halal products, claimed to be halal has been circulated in the Muslim market and remains unsolved. It would always link to how supply chain management (SCM) may incorporate sustainability and Halalan Toyyiban (HT). Knowledge is the main resource and essential for the organisation and people. Unsuccessfully disseminating knowledge to ensure adherence to the standards of HT across all stakeholders needs to be resolved immediately. This is only a concept paper; hence the purpose of this paper is to reveal that SCM would utilize artificial intelligence (AI), to successfully disseminate knowledge and taking advantage of advanced technology, big data and users. The initial concept was developed by use of a literature review of the AI-based Sustainable Halalan Toyyiban Supply Chain Knowledge Dissemination System (AiBas-HalaToyib-SCKnoDeS). The key concept can be used by organizations in developing AiBas-HalaToyib-SCKnoDeS. The result of AiBas-HalaToyib-SCKnoDeS is an interesting area for fut ure research. However, the current concept of value underlies its offering organizations as a starting point. This conceptual model fills important gaps in ethical and sustainable supply chain management that are in line with Halalan Toyyiban's requirement s, laying the groundwork for further study and real- world application.